Flexural behavior of shield tunnel lining segments reinforced using grouted channel steel: Experimental investigation - Kan Huang; Xun Wu; Jun He; Bin Huang; Yi Peng; Kaidi Zhou (Case Studies in Construction Materials)
This study examines a reinforcement method using grouted channel steel for damaged shield tunnel lining segments in urban rail transit systems. Full-scale experiments were conducted to analyze the flexural failure mechanism and evaluate the performance improvement of damaged segments before and after reinforcement. The results demonstrate the effectiveness of the proposed method in enhancing structural capacity and extending service life. Underpinned by the elastic and plastic theory, a calculation method has been developed to identify the cracking load and load-bearing capacity of segments before and after reinforcement. This method has been further validated through comparisons with full-scale loading tests. Results indicate that the grouted channel steel reinforcement could significantly enhance the load-bearing capacity of damaged segments, the ultimate load has been promoted by approximately 33 % and the ultimate deformation resistance has been improved by 57.3 %. The method effectively prolongs the elastic and plastic phases of damaged segments while limiting crack width growth. The discrepancy between theoretical calculations and experimental results is within 10 %, demonstrating high accuracy. The developed calculation method provides a reliable strategy to evaluate the structural condition of tunnel segments under diverse loading conditions, both before and after damage and reinforcement.